Structural unemployment among youth in Malaysia: causes and cures/ Thirunaukarasu Subramaniam - Subramaniam, Thirunaukarasu (2002)
Youth unemployment is a common phenomenon in developed and developing countries. Youths are a group of people who always exhibited a marginal attachment to the labour market. The reason for this marginal attachment is due to their transition from the schooling to the working environment. The objective of the paper is to analyse the existence of the problem of unemployment mainly structural in nature among youth in Malaysia. Data collected from secondary sources obtained from Social Statistics Bulletin and Yearbook of Statistics, Malaysia. The major reason for youth unemployment is due to mismatch between skill acquired and the availability of job openings in the labour market or widely known as structural unemployment. Due to globalization, slowdown of an economy will also have adverse impact on its trading partners. The recent economic slowdown in the United States for example led to the decline in the exports of manufacturing goods from Malaysia and further aggravated the problem of unemployment in Malaysia. Thus, it can be said that failure for proper manpower planning is the reason for structural unemployment. The authority failed to identify the need of human resources in various sector and to properly address the issue of human resource planning in the macro context. Reskilling, retraining and relocation are possible solutions for unemployment problem among youth in Malaysia.